تمثلات المرأة التبسية لبعض المعتقدات الشعبية - دراسة أنثربولوجية بمدينة الشريعة - - نسيمة حميدة (My University, 2017)
The culture in its vastest sense included all the faces of the material life, The behavior, the relations and the regulations and all which is useful for a society in its internal and external relations, which is clearly highlighted in the practices of the individuals including popular beliefs, Subject of our study marked so:” Representations of the Tebessian woman of certain popular beliefs, anthropological study in the city of Chéria “ ,That we studied according to four complementary frames which are: The methodological frame, the theoretical frame, the operational frame and the analytical frame. The methodological frame contains the problem of our study with its needs which are a part of reasons of our choice of the subject, Its objectives, its importance and its approach besides the methodological approach which contains the program of the anthropological study, techniques and models of the methodology, follow the spaces of the research which are: Human and temporal, Then the central concepts of the research and the most important previous studies. As for the theoretical and practical frame, it consists of the theoretical material in parallel with the elements of the practical work which appears at the level of four chapters which combined between the theoretical material and the practical elements. As for the analytical frame, it contains the analysis of the practical elements and their interpretation by arriving at the general results of the thesis which answered the problem of our thesis by ending in the Representations of the woman in popular beliefs that we studied on the ground.